Influence of winter temperature and spring ice melt on the reproductive performance of Mute Swans Cygnus olor nesting on offshore islands at the northern edge of its breeding range - Kouzov, Sergey A.; Kravchuk, Anna V.; Abakumov, Evgeny V.; Kouzova, Nadezhda I. (Wildfowl, 2024)
The influence of winter temperature and spring ice melt on Mute Swan Cygnus olor abundance and productivity in a northern part of its breeding range was studied using data from 831 nests on the Kurgalsky Peninsula, in the Russian part of the Gulf of Finland, during 2006–2021. There was marked annual variation in the numbers of breeding pairs, which ranged from 17–95 per year over the 16-year study, with greatest numbers observed in years with early ice melt in the gulf. Birds nested either territorially or in colonies. Nest sites were categorised as being occupied for either short-term or long-term periods, with the latter considered likely to include cases of the same pairs nesting at the same sites over several years. Clutch sizes and hatching success were greater for territorial pairs and for those on long-term sites compared to pairs on short-term and colonial nests. Overall hatching success decreased in years with later ice melt.